Impression Management at Work: Intentions of Casual Workers: Impression Management at Work: Intentions of Casual Workers - Ukpere, Wilfred; Mapira, Nyasha; Mitonga-Monga , Jeremy (Annals of Spiru Haret University. Economic Series, 2024)
The purpose of this study was to investigate why casual employees at a global firm in Zimbabwe engaged in impression management. This exploratory qualitative study investigated casual workers’ intention for engaging in impression management at the case global firm in Zimbabwe using the interpretivism research philosophy. Face to face, semi-structured interviews were used to collect data from ten research participants who had been employed by the global firm in Zimbabwe for a minimum of five months. The study found that casual workers at the case global firm in Zimbabwe are driven to control their work impressions to preserve their good reputation, build social capital, and accomplish career-related objectives including moving up the corporate ladder, receiving high performance reviews, obtaining a permanent position, and getting promoted. Therefore, as it is, casual workers at the case global firm in Zimbabwe use impression management tactics with the overall aim of maintaining job security. The current study recommends that casual workers should identify the circumstances in which impression management is most appropriate and make an effort to become more aware of when and how often to manage impressions. They could do this by practicing self-monitoring, receiving feedback, or participating in other professional development activities. The study also urges managers at the global firm in Zimbabwe to encourage workers to utilize impressions that are authentic and discourage employees from managing images that are destructive to the organization.